Development of patient-centered outcomes for labour and birth: a qualitative study - Geoffrey E. Johnson; Lauren Kan; Jennifer Nguyen; Kim Campbell; Laura Ralph; Nicole Koenig; May Sanaee; Ciana Maher; Geoffrey W. Cundiff (Clinical and Experimental Obstetrics & Gynecology)
Background: Current quality improvement models in obstetrics focus on prevention of adverse perinatal outcomes. The development of these metrics was based on expert opinion that did not account for patients’ values. The ultimate aim of our research is to develop performance indicators for labour and birth that reflect the patient perspective. Methods: A qualitative interview design was used to engage a convenience sample, of recent (<1 year) postpartum patients, in semi-structured interviews, where they shared their experiences of their recent birth. Patients were also asked to assess descriptions of adverse perinatal outcomes for readability and comprehension, towards developing accurate unbiased descriptions for a subsequent survey of patients to weight complications. Responses were recorded, transcribed, coded and analyzed using thematic analysis. thematic analysis. Results: Five themes emerged during the analysis: (1) desire for patient-centred care, (2) improved communication, (3) labour/birth, expectations and outcomes, (4) care team support during labour and birth, (5) continuing emotional and physical postpartum care. Conclusions: Patient-centred care and good health outcomes were the major values expressed by the patients in this study. Good communication and shared decision making led to patients describing their labour and birth as a satisfying experience. This study lays the foundation for developing a quality tool to measure the outcomes of birth and adverse outcomes from the patients’ perspective.